2006
DOI: 10.1016/j.molcel.2006.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Occupancy Profile of Mediator and the Srb8-11 Module Reveals Interactions with Coding Regions

Abstract: Mediator exists in a free form containing the Med12, Med13, CDK8, and CycC subunits (the Srb8-11 module) and a smaller form, which lacks these four subunits and associates with RNA polymerase II (Pol II), forming a holoenzyme. We use chromatin immunoprecipitation (ChIP) and DNA microarrays to investigate genome-wide localization of Mediator and the Srb8-11 module in fission yeast. Mediator and the Srb8-11 module display similar binding patterns, and interactions with promoters and upstream activating sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
101
6
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 44 publications
13
101
6
2
Order By: Relevance
“…However, recent results suggest that the kinase module can play a role in transcriptional activation as well as repression (20,21). An exclusively repressive function would be difficult to reconcile with the observation that the genome-wide occupancy profiles of Cdk8 and Med13 characterized by ChIP match that of the core mediator complex (69,70). Our results support an essential and direct function for the Med12 and Med13 subunits in the activation of Wg target genes.…”
Section: Discussionmentioning
confidence: 51%
“…However, recent results suggest that the kinase module can play a role in transcriptional activation as well as repression (20,21). An exclusively repressive function would be difficult to reconcile with the observation that the genome-wide occupancy profiles of Cdk8 and Med13 characterized by ChIP match that of the core mediator complex (69,70). Our results support an essential and direct function for the Med12 and Med13 subunits in the activation of Wg target genes.…”
Section: Discussionmentioning
confidence: 51%
“…In contrast, another study found Mediator to be associated with upstream regions of a large number (Ϸ1,200) of genes, and with coding sequences of many genes, in yeast grown in CSM (26). Similarly, Mediator association with a large number of both intergenic regions and coding sequences was reported in fission yeast (Schizosaccharomyces pombe) (43). More recently, comparison of Mediator association at promoters in yeast grown in YPD and in CSM suggested that although differences in growth conditions could account for a small proportion of the discrepant results published previously, the greater portion of the discrepancy could not be explained in this way (42).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, genomewide profiling indicates that Mediator can associate with gene-coding regions, suggesting that a portion of copurifying Mediator may even be in elongating pol II complexes (36,37). Purification of a tagged Mediator subunit under cross-linking conditions might distinguish between some of these possibilities.…”
Section: Discussionmentioning
confidence: 99%